(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
In this presentation I will be attempting to think about some questions that occur to me as significant in thinking about the ever changing relationship between technology, and psychological and social systems, and how that might impact upon our practices as psychotherapists.